Prevalence of cutaneous hypersensitivity to Aspergillus fumigatus in patients with asthma in the central part of Karnataka and its impact on asthma severity - Bondade K; Ajit E; Raikar PS; Srinivas K; Banur A; Angadi S (Journal of Medical and Scientific Research, 2025)
Introduction: Severe asthma is particularly linked to atopic conditions, especially to mold allergens like Aspergillus fumigatus. Allergic bronchopulmonary aspergillosis is an immunological lung disorder, with initial phase of hypersensitivity to Aspergillus (AH). This study aimed to assess Aspergillus sensitization among asthmatic patients through cutaneous hypersensitivity testing at our tertiary care center in central Karnataka.